High School Students’ Perception on The Implementation of Full Day School - Roslina, Roslina (CV. Ridwan Publisher, 2021)
The purpose of this study was to determine students' perceptions related to the implementation of FDS (full day school) and Want to know also how to implement FDS in SMA 2 Kolaka. The population of this study were all students of grade 2 and 3, SMA Negeri 2 Kolaka consisting of 100 students. The sample of this study was 100 students, namely grade 2 and 3 students. There are two types of instruments in this study, Questioner and interview. Questioners divided into grade 2 and 3 students in the questionnaire. There are two first parts, positive perception 8 questions, two negative perceptions, 8 questions, so the total is 16 questions, after that the interview is done after all the questionnaires are given. All data obtained in this study were analyzed using the formula, the value for the answer yes is 1, and while the value for no is 0. Yes = 1x100 = 100%, No = 0x100% (no need to be counted), then the data from the results is added Interview. Based on the findings from this study it can be concluded that most students agree with the implementation of FDS in their school. This is supported by the results of the questionnaire (see 4.1) which shows that 62% of the 100 students agreed with the full day of school implementation and 38% disagreed and were also supported by records of interviews with researchers named Andi Nur Fadillah rahma yatte class XII IPA 1, he said to myself I really agree with the implementation of full day school, in my school because in addition to extra extracurricular hours for a full day my character really formed because of extra curricular hours, and I felt my fashion was more orderly and good